MODELLING OF OIL SUSPENSION PROPAGATION IN A LONG DISTANCE HILLY TERRAIN PIPELINE - Ridwan Reza Nugraha, Muhammad
Oil is usually transported from oneplace to another in the form of suspension, which is a mixture of water and oil. The suspension flows in the pipeline driven by pressure drop between an inlet and an outlet. Knowing suspension arrival time at the outlet is important for the efisien of pump activity. In this study, the head and tail position of the suspension at any time will be calculated by taking into account pressure and pipe geometric. The suspension flow models are governed by second order ordinary differential equations and then solved by using finite difference method. In this model there are two unknown parameters, friction force due to pumping equipment and shear stress of turbulent flow, that should be estimated. Genetic algorithm is used to estimate those parameters.